DESKRIPSI KEMAMPUAN LITERASI SAINS SISWA KELAS XII IPA 1 DI SMA MUJAHIDIN PONTIANAK PADA MATERI LARUTAN ASAM BASA - Ahmad Ahmad; Eny Enawaty; Ira Lestari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThis research aimed to describe the science literacy of twelve grade students of science class in SMA Mujahidin Pontianak on  Acid-Base Solution subject matter. The method used in this research was descriptive. The data were collected through purposive sampling technique with 31 participants of twelve grade students of science class. The tools that were used in gathering the data were test and interview guidelines. The science literacy that were measured content, process, and context of science. Based on the research findings, the students had a medium science literacy (19,35%) and a low science literacy (80,65%). Most of the students tend to learn by memorizing in which may affect them to have a less understanding the concept and in applying the acid-base solution material. It was found also that most of students could only used the basic concept but had a difficulty in using the complex one. Students can used the concept of the material in everyday life if they have a well understanding of the concept itself.    Keywords: science literacy ability, medium science literacy, low science literacy, acid-base solution